Analisis Kemampuan Guru PAI dalam Menyusun Instrumen Penilaian Ranah Afektif di Madrasah Aliyah Syamsuddhuha Dewantara, Aceh Utara - Abdullah, Khadijah Razali; Yusnaini, Yusnaini (Pascasarjana IAIN Lhokseumawe, 2024)
Affective assessment is a crucial component of Islamic education, as it plays a significant role in shaping students’ character and moral values. However, in practice, affective assessment is often overlooked or conducted without a systematic instrument. This study aims to analyze the ability of Islamic Education (PAI) teachers to develop affective assessment instruments at Madrasah Aliyah Syamsuddhuha Dewantara, North Aceh. This research employs a descriptive qualitative approach through a field study. The subjects were PAI teachers teaching in grades X, XI, and XII. Data were collected using observation, in-depth interviews, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and methods. The findings reveal that while PAI teachers are aware of the importance of affective assessment, they still face challenges in designing valid and structured instruments. Some teachers have begun implementing procedures such as formulating indicators, drafting statements, and developing scoring rubrics, but these efforts are not yet consistent. Affective assessment is still predominantly conducted through informal observation, without supporting documentation that can be accounted for administratively. This study highlights the urgent need to enhance teachers’ competence in developing affective assessment instruments. Proper and systematic assessment not only improves evaluation quality but also strengthens the goals of Islamic education in nurturing students with noble character and integrity.